Analisis Tentang Pendidikan Karakter Yang Terdapat dalam Surat Luqman Ayat 12-19 (Kajian Tafsir Al-Azhar) - Rafki Parifia; Adam Jakrinur; M.Ari Khairan; M.Taura Zilhazem; Wismanto Wismanto (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
The background of the problem in this research raises the values of Islamic education contained in Q.S Luqman verses 12-19 which are guidelines for humans which are used as the foundation and basis for educating humans on the right path. This article aims to explore character education from an al- -Qur'an through al-Azhar interpretation, so that understanding of character education is more varied and more comprehensive. The aim of this research is to reveal the form of character education carried out by Nabiyullah Luqmanul Hakim as contained in Q.S. Luqman verses 12-19. The research method used is library research, the data of which is obtained from literature studies with a theoretical and philosophical approach. The results of the research found that the character education values contained in Q.S Luqman verses 12-19 Tafsir Al-Azhar by Hamka are the value of gratitude, the value of prohibiting kufr, the value of monotheism, the value of prohibiting shirk, the value of honoring both parents, the value of obeying both parents. , the value of believing in the Day of Judgment, the value of commanding prayer, the value of doing what is good and preventing what is wrong, the value of patience, the value of prohibiting arrogance, the value of simplicity in social life.